The Role of Emotional Intelligence in Mathematical Critical Thinking: A Systematic Literature Review - Tanjung, Winda Khadijah Ashareni; Jupri, Al; Usdiyana, Dian (Jurnal Pendidikan MIPA, 2025)
Critical thinking ability is a fundamental ability in the process of developing other thinking abilities in improving students' intellectual abilities, especially in learning mathematics.  One factor that influences critical thinking skills is emotional intelligence, especially awareness of controlling one's emotions. This research aims to apply a literature review in analyzing mathematical critical thinking skills in terms of emotional intelligence. The research method used in this research is a Systematic Literature Review (SLR) by reviewing relevant literature regarding critical thinking abilities in terms of emotional intelligence. Data collection was carried out through article searches using Publish or Perish on Google Scholar, Scopus, and Semantic Scholar with a publication range from 2015 to 2024. Article selection was carried out based on inclusion and exclusion criteria to obtain 10 journals that were relevant and suitable for further analysis. Based on the results of the analysis, it show that: (1) The type of research that is most widely used is quantitative, whereas other types of research are the qualitative and mixed method; (2) Most levels of education are at the junior high school level while other levels include elementary school, high school, and university students (3) Emotional intelligence has a positive relationship with students' mathematical critical thinking abilities (4) Factors that influence students' critical thinking abilities in terms of students' emotional intelligence are negative emotions such as stress, and frustration and negative thoughts that dominate and limit students' abilities. Based on research findings, good emotional handling strategies are needed in the learning process so that students can develop critical thinking skills optimally. Future research could explore more deeply the mechanisms of how emotional intelligence influences mathematical critical thinking abilities, as well as examine the effectiveness of interventions designed to improve emotional intelligence and mathematical critical thinking abilities simultaneously.        Keywords: mathematical critical thinking ability, emotional intelligence, systematic literature review.